Gene Polymorphisms Affecting the Pharmacokinetics and Pharmacodynamics of Donepezil Efficacy - Lu, Jin; Wang, Xiuzhe; Wan, Lili; Fu, Jianliang; Huo, Yan; Zhao, Yuwu; Guo, Cheng (Frontiers in Pharmacology, 2020)
Donepezil (DNP) is the first-line drug used for Alzheimer’s disease (AD), however, the therapeutic response rate of patients to DNP varies from 20%-60%, the main reason for the large differences in the clinical efficiency of DNP therapy are closely related to genetic factors, some of which are pharmacokinetics(PK)-related genes while others are pharmacodynamics(PD)-related genes. Thus much emphasis has been put on the investigation of an association between the related PK and PD gene polymorphisms and the therapeutic response of DNP, but a consistent view does not yet exist. In this review, we summarize recent findings regarding the genetic factors influenced the clinical efficacy of DNP, where larger individual differences are seen as a consequence of polymorphic alleles with CYP2D6, CY3A4, CY3A5,APOE, ABCA1, ABCB1,ESR1, BCHE, PON-1, CHRNA7 and CHAT. We also discuss possible strategies for the evaluation of clilincal efficacy of DNP, with a specifical focus on possible biomarkers of PK / PD, and reflect the perspectives and the limitations of the field, which will also be beneficial to understand the multiple mechanisms of DNP therapy to AD.